La communauté linguistique kanak en Nouvelle-Calédonie entre passé et avenir - Françoise Roche (Lengas)
The Kanak speech community in New-Caledonia shares twenty-eight native languages, plus one Creole and one Slang, both of them very recent, as well as two varieties of French, and its speakers are frequently bilingual or multilingual. This multiplicity is the result of historical evolution,through a process of diversification of original languages as through their preservation in front of the French language domination. According to the UNESCO, more than half of the Kanak languages are endangered, however most of them show resiliency and their present and future preservation will largely depend on their speakers' loyalty and resistance. Thus, not only historical but also geographical factors are at work, here.Then, how does the concept of speech community apply to the Kanak sociolinguistic situation? Are we to infer that sharing a common local French language is what unites this linguistic community, or, on the contrary, that there are as many speech communities as spoken languages, regardless of the number of speakers?